KUALITAS PELAYANAN PUBLIK DALAM PENGUJIAN KENDARAAN BERMOTOR PADA DINAS PERHUBUNGAN KABUPATEN PATI - Raden Adi Prasasto Aris Triharyanto (Master of Public Administration, Universitas Slamet Riyadi, 2018)
Prasasto & Triharyanto, 2018. “The Quality Of Public Service In MotorVehicle Testing At Department Of Transportation Pati”. Slamet RiyadiUniversity. Theses, unpulbished.This research aims to get an idea of the quality of public services. Thisresearch is qualitative research using a descriptive approach. Method ofcollecting data through observation, interview and documentation which ismeasures konprehensif. Research results retrieved 1) Utilizing existingproduction in the form of capital budget activities for the gross of the originalarea, 2) Utilizes a standard Operational Procedures to improve publicservices, 3) increases the availability of the means and infrastructure toprovide a sense of Justice to the community over the cost to test and rate 4)utilize the communication strategy in the form of call center complaints tocapture and provide answers to public complaints quickly.Keywords: Quality Of Service,